For God and the fatherland : religion and politics in Argentina - Burdick, Michael A., 1953- (SUNY series in religion, culture, and society., 1995)
"Title is somewhat misleading. While the work presents information on the conflict between church and state in the 1880s and examines the Perón regime's relationship with the Church, the heart of the book is much more tightly defined. Presents a detailed and sympathetic picture of the Movement for Priests of the Third World, a leftist tendency within the Church that favored peronism, during the 1960s-70s"--Handbook of Latin American Studies, v. 58.